2021
DOI: 10.1007/s00267-021-01570-y
|View full text |Cite
|
Sign up to set email alerts
|

Long Arm of Motorway—The Impact of Fenced Road on the Mortality of European Badgers

Abstract: We studied the impact of the new fenced and accident-safe motorway on the mortality of European badgers Meles meles on local roads in western Poland in 2010–2015. We monitored the badgers mortality on local roads of three categories: main roads, secondary roads and county roads. The study was conducted before and after the opening of the motorway in 2012. We hypothesized that the mortality of badgers is lower due to traffic concentration on motorway. Ninety two badgers were killed in collisions with vehicles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The prevalence of physical mitigation measures, i.e., fences and wildlife crossings likely stem from the fact that these are convenient solutions and do not require any sacrifices from the drivers' side. Our results showed that these measures increased the confidence of the drivers, however they were not fully aware the limitations of these (see also Cserkész et al, 2013;Nowakowski et al, 2022). A fence installation on its own can decrease the risk of AVCs with large mammals by 54%, and with the addition of a wildlife crossing, this risk can be reduced by as much as 83% (Rytwinski et al, 2016).…”
Section: Opinion On Avc Preventionmentioning
confidence: 72%
See 1 more Smart Citation
“…The prevalence of physical mitigation measures, i.e., fences and wildlife crossings likely stem from the fact that these are convenient solutions and do not require any sacrifices from the drivers' side. Our results showed that these measures increased the confidence of the drivers, however they were not fully aware the limitations of these (see also Cserkész et al, 2013;Nowakowski et al, 2022). A fence installation on its own can decrease the risk of AVCs with large mammals by 54%, and with the addition of a wildlife crossing, this risk can be reduced by as much as 83% (Rytwinski et al, 2016).…”
Section: Opinion On Avc Preventionmentioning
confidence: 72%
“…This perceived security and the relatively low number of AVCs along first-class roads made some drivers to overlook the importance of protective measures against AVC. Although this is partly a misconception, as even the fences can't guarantee complete protection from AVCs (Cserkész et al, 2013;Nowakowski et al, 2022). In fact, as Cserkész et al (2013) noted, 5% of traffic accidents on Hungarian first-class roads are caused by AVCs, emphasizing the need for extra precautions and the importance of additional protective measures along roads.…”
Section: Attitude Towards Nature Conservation and Traffic Safety Aspe...mentioning
confidence: 99%
“…However, it seems that in some countries, these proportions are similar and distributed more reasonably. In western Poland, between 2010 and 2015, road mortality of badgers (excluding motorway opening effect) did not differ between years [ 169 ]. In relation to the data presented above, Poland belongs to a group of countries with very high hunting bag growth ( Table 3 ).…”
Section: Trendsmentioning
confidence: 99%
“…In relation to the data presented above, Poland belongs to a group of countries with very high hunting bag growth ( Table 3 ). In line with country-dependent high hunting bag increases, there are no papers reporting an adequate increase of collisions with badgers greater than 100–200% in recent years [ 166 , 167 , 168 , 169 ]. Comparing these data with the rapidly and sharply increasing hunting bag, a question arises–is the badger population in some countries currently overhunted?…”
Section: Trendsmentioning
confidence: 99%